Comment on “Fertilization and pH effects on processes and mechanisms controlling dissolved inorganic phosphorus in soils” by Nicolas - Lumsdon, David G. (Geochimica et cosmochimica acta, 2012)
In a recent article by Devau et al. (2011) a mechanistic model based on a surface complexation theory is presented which aims to predict the solubility of inorganic phosphorus (P) in soils. Compared with many empirical soil studies, the surface complexation approach as applied to soils is to be encouraged since it provides a coherent and mechanistically based foundation for the interpretation of a wide range of soil chemical phenomena. Soil chemists have attempted to explain P solubility for decades, so Devau et al. (2011) have attempted a difficult task but unfortunately they have introduced a number of errors that need to be corrected. The purpose of the present contribution is to suggest some corrections to their proposed model and provide commentary on the errors and inconsistencies concerning the application and citation of the sources of thermodynamic data. Hopefully this will provide some insights for others wishing to progress this subject.